Reflections from the Journal of Turkish Librarianship, Living Its Golden Year - Oya Gürdal (Türk Kütüphaneciliği)
The most specific characteristic of publishing is no doubt, creativity. Escarpit, describes publisher as a “midwife”. Actually there happens a labor. For this re- ason it is painfull and has risks as evey labor. Thus, the journal of Turkish Librarianship which is the publish of Turkish Library Association, performs this uni- que phenomenon, the “ labor fac t” since 50 year s for its readers. It shares the hapiness of labor both with its authors and readers. The paper, calls collegues and readers of the journal, to think about the requirement ofhow to enrich it by context. For instarıce supporting it with articles re- fering to intellectual ejforts and theoreticalparadigmas, and also about the ways how to increase its usage. At the same time the paper concerns data about “cita- tion analysis” based on last decade of the Journal o/Turkish Librarianship refe- ring its usage.